PELATIHAN PUBLIC SPEAKING MELALUI EMPAT METODE KOMUNIKASI SEBAGAI UPAYA PENGEMBANGAN DIRI GURU - Pratiwi, P.A.A.S.; Dewi, A.A.S.S.S.; Setianingsih, N.K.A.I.; Dananjaya, N.S. (Buletin Udayana Mengabdi, 2023)
In the era of industry 4.0, everyone must increase their own self-value to be able to compete with other individuals in terms of communicating with public, especially for teachers. To be able to deal with all situations in the classroom during learning and to deliver the material as well as to create a pleasant learning atmosphere, teachers are expected to master good public speaking techniques. With teachers’ public speaking skills are increasing, they can be more confident when teaching in the class and transferring knowledge to their students. In addition to delivering the material, in the community service activity also conducted question and answer sessions, drill, observation, reflection, and feedback. Introduction to the community service team and participants, explanations of informative, persuasive, and entertaining public speaking, practices, as well as question and answer session were done at the first day of the community service. On the second and third day of training, there were presentations of public speaking material related to teaching and learning. On the fourth and fifth days, teachers’ micro teaching presentations and evaluations were held. The community service activities went well. After participating in the activities and training, all 33 participants were able to master the material presented, use public speaking language well, know the appropriate presentation method, and master body language and vocal expressions. Through public speaking training, the teachers are able to support the teaching and learning process in schools. Keywords : Public Speaking, self-development, teacher, communication method.